Laboratory Medicine at the Crossroads: Integrating Genomics, Big Data, and Point-of-Care Testing for Improved Outcomes - Alghamdi, Mohammed Abdualrhman; Alwaaylee, Wael Ali Hamed; Hamad, Ashwaq Essam Sadiq; Alzahrani, Khaled Swaylem Mohammed; Assiri, Younis Ibrahem Mohammad; Aseeri, Abdulrhman Mohmmed Ahmed; Alqarni, Abdullah Mari Moraya; Alshaikhi, Aqeel Ali (Journal of Posthumanism, 2024)
This article reviews the transformative role of laboratory medicine at the intersection of emerging technologies and healthcare innovation. The integration of genomics, big data analytics, and point-of-care testing (POCT) has redefined diagnostic strategies and patient management, offering unprecedented opportunities to enhance precision medicine and healthcare outcomes. By examining recent advances, challenges, and future directions, this review highlights how laboratory medicine is transitioning from traditional centralized models to dynamic, technology-driven approaches that empower clinicians, patients, and health systems. It underscores the importance of data interoperability, workforce training, and ethical considerations in maximizing the potential of these innovations.